Being subordinate men: Paul's rhetoric of gender and power in 1 Corinthians - Robinson, Brian J. (Fortress Academic, 2018)
Being Subordinate Men offers a gender critical examination of Paul's use of gender and power in the argument of 1 Corinthians, showing that the apostle consistently undermines first-century Roman norms of masculinity.